Comparación de las características fisicoquímicas y composición de ácidos grasos de los aceites en las semillas en dos estados de madurez del almendro malabar (Terminalia catappa) en Iquitos – 2023 - Soto Andrade, Martín Arón (2023)
The purpose of the present investigation was to compare the physicochemical properties and the composition of fatty acids of the oils of the seeds of two stages of maturity of the malabar almond tree (Terminalia Catappa). The type of study was descriptive comparative. The samples of the fruits in two states of maturity (semi-ripe and mature) were selected from existing trees as ornamental plants in the streets of the city of Iquitos, located in the province of Maynas -Loreto Region. The results obtained from the oil content for fruits in the semi-ripe state is 44.94 % and for the fruit in the mature state it is 55.59 %. The comparison of the results of the physicochemical characteristics of the oil from the seeds in two stages of maturity of the Malabar almond tree (Terminalia Catappa), are different, it was observed that: the acidity index is 3.80 and 180.80 mgKOH/g ; saponification value 306.70 and 263.77 mgKOH/g; peroxide index 207.98 and 58.37 meqO2/Kg; and saponification values 306.70 and 263.77% mg KOH/g oil. The composition of fatty acids was determined by gas chromatography, mainly stearic acid representing 4.67 % of the total fatty acids in semi-ripe fruits and 5.04 % in mature fruits, the presence of oleic acid from 30.67 % for semi-ripe fruits and 26.32 % at maturity, in addition to other unsaturated fatty acids such as palmitic acid and linoleic acid.